The Effect Of Nutrition Intervention Education Using Video Explainer Media On Mother’s Knowledge And Attitude About Stunting Prevention In Posyandu Banjar Tubuh Blahbatuh - Ni Putu Widya Putri Laksmidewi; Miftakhur Rohmah (Journal of Health Science Community, 2025)
Mother’s knowledge and attitudes are one of the things that influence the growth status of toddlers. In fact, the lack of knowledge and attitudes of mothers to prevent stunting is still a problem today. The research aims to determine the effect of nutritional intervention education using video explainer media on mothers’ knowledge and attitudes regarding stunting prevention at Posyandu Banjar Badan Blahbatuh. Quantitative research, using the Pre-Experiment method with one group pre-test and post-test design. Using the Purposive Sampling technique, a sample of 30 respondents was obtained. The independent variable was nutritional intervention education using explainer video media, and the dependent variable was mother’s knowledge and attitudes regarding stunting prevention. The Wilcoxon correlation test was used to determine the effect of education provided on maternal knowledge and attitudes. The results of research on mothers’ knowledge before being given education were 18 people (60%) categorized as sufficient. After being given education, 30 respondents (100%) were categorized as good. Attitudes before being given education were in 19 positive categories (63.3%) after education became 24 (80%) in positive categories.Wilcoxon analysis resulted in p-value = 0.000 <0.05, meaning that H1 was accepted, there was an increase in mother’s knowledge and attitudes after being given education. Mother’s knowledge and attitudes are influencing factors in preventing stunting. By providing nutritional intervention education using video explainer media about preventing stunting, mother’s knowledge and attitudes will increase.